Strategi Pengembangan Usaha Kerajinan Alat Musik Tradisional Pada UKM ‘Ardi Laras’ Sebagai Produk Unggulan Kabupaten Kutai Kartanegara - Ningsih, Nurhayati; Erwinsyah, Erwinsyah; Suprapto, Heru (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2018)
Abstract:            In the District of Kutai Kartanegara sector of business that has great potential to be harnessed, that is the traditional musical instrument crafts "Ardi Laras". This is a very great opportunity attempts, because we know the Kutai Kartanegara region has a very high art culture among others dances, music, theatre, Kroncong music community they need roads and musical instruments. The purpose of this research is to find the location of the position of Traditional musical instrument Crafts quadrant ' Ardi Laras ', and CSF analysis to find out the factors of traditional musical instrument crafts victories.Based on the results of the research of the development strategy of SWOT analysis has been performed on the Traditional musical instrument Crafts ' Ardi Laras ' position matrix on the strategy of aggressive on quadrant i. Then a strategy can be done that is to put forward the values of tradition, partnering with agencies and schools so that will add to the number of musical instrument production, improve product quality, and more enterprising introduce products.Further on the results of the analysis of the CSF (Crtical Success Factor) benchmark the success of Traditional musical instrument Crafts ' Ardi Laras’ is a.    Product safety of instrument design that made such timber should pay attention to the smooth so as not to injure the hand as well as the installation of a neat nails and other supporting materials.  b.    For durability of a product that must be considered is the raw material used must be strong and not easily broken when used. c.     The similarity of price with the quality of the product provided it means Crafting Traditional Instruments ' Ardi Laras' more attention to comfort, security, durability, and design the product so that the price offered did not disappoint the consumer.Keywords: traditional music instruments, strategies, SWOT, CSF.